2001
DOI: 10.2527/2001.794919x
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable fiber fermentation by gut microflora from canines.

Abstract: The objective of this study was to assess fermentability by canine gut microflora to include shortchain fatty acid (SCFA) production, organic matter (OM) disappearance, and gas production of vegetable and fruit fiber sources compared to fiber standards (psyllium, citrus pectin, and Solka Floc). Fiber sources included apple pomace, carrot pomace, flaxseed, fruit blend (mixture of peach, almond, nectarine, and plum), grape pomace, pea hulls, pistachio, and tomato pomace. Substrates were fermented in vitro for 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 22 publications
8
40
3
Order By: Relevance
“…Average SCFA production for NCF was 467.1, for HCF, 527.5, and for HECF, 352.4 µmol/g of DM. These values are similar to those for xanthan gum (500 µmol/g of OM) (28). Total SCFA production was higher in some samples with lower SDF concentrations, which can seem contradictory.…”
Section: Resultssupporting
confidence: 81%
“…Average SCFA production for NCF was 467.1, for HCF, 527.5, and for HECF, 352.4 µmol/g of DM. These values are similar to those for xanthan gum (500 µmol/g of OM) (28). Total SCFA production was higher in some samples with lower SDF concentrations, which can seem contradictory.…”
Section: Resultssupporting
confidence: 81%
“…In rodent studies that used a purified diet and demonstrated anti-inflammatory effects of fermentable fibers, the ratio of fermentable fiber to cellulose was mostly 1:1 or 2:1, with equal intake of two types of fiber or twice as much fermentable fibers. Although fermentability and solubility are two different approaches used to classify fibers, fermentable fibers are usually soluble, whereas insoluble fibers such as cellulose usually have poor fermentability (18). In the United States across a wide range of total fiber intake, the intake ratio of soluble to insoluble fiber was reported to be w1:2-1:3 (62,63), falling short of the intake of fermentable fiber used in the animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although carbohydrates in general are an important source of energy for intestinal microflora (12,13), various fibers show different fermentation potentials (14)(15)(16)(17). Overall, cellulose (b-glucan) in the standard rodent diets showed poor fermentability (17,18), whereas similarly glucose-based resistant starch is readily fermentable (17). Fructose fibers of varying polymer size are fermented at different rates (16,19).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Chemical composition and fermentative characteristics of several fruit pomaces were studied using a canine in vitro model [17]. Total dietary fiber concentration varied among the different pomace sources; apple pomace had the greatest TDF concentration (79%), whereas grape pomace had the lowest (55%), tomato pomace and fruit blend (mixture of peach, almond, nectarine and plum) had intermediate values, 57% and 65%, respectively.…”
Section: Alternative Dietary Fiber Sources In Companion Animal Nutmentioning
confidence: 99%
“…In general, fruit fibers with a greater insoluble:soluble fiber ratio had lower gas production and SCFA production after 12 or 24 h of in vitro fermentation. After 24 h of fermentation, apple pomace had a greater total SCFA concentration (2.1 mmol/g) in contrast to grape pomace, which had the lowest concentration (0.83 mmol/g) [17]. Sunvold et al [12] evaluated in vitro fermentation characteristics of several dietary fiber sources, including citrus pulp and citrus pectin, using fecal inoculum from cats, dogs, horses, pigs, humans and cattle.…”
Section: Alternative Dietary Fiber Sources In Companion Animal Nutmentioning
confidence: 99%